Effect of triple antibiotic paste and calcium hydroxide as intracanal medicaments on bond strength of composite to dentin - Zare Jahromi, Maryam; Mirzakouchaki, Parvin; Barekatein, Mehrdad; Akhtari, Marziyeh; Riazifar, Negin; Ranjbarian, Parisa; Saee, Mohammad-Reza (Journal of Dental School, 2019)
Objective: Considering the use of triple antibiotic paste (TAP) for root canal treatment of open apex teeth, this study aimed to assess the effect of TAP and calcium hydroxide (CH) on bond strength of composite to dentin. Methods: This in-vitro study was conducted on 32 extracted human premolar teeth. After disinfection with 2% thymol solution, the enamel on the buccal surface of specimens was removed to expose a smooth dentin surface parallel to the long axis of the teeth with approximately 19mm2 surface areas. Specimens were divided into three groups of 11, 10 and 11 specimens. In group one, TAP, in group two CH and in group three, saline solution were applied to dentin surfaces for 14 days. After removal of medicaments, composite cylinders were bonded to the dentin surfaces using a bonding agent. Shear bond strength was measured in an Instron machine at a crosshead speed of 1mm/min. Data were analyzed using one-way ANOVA. Results: The highest mean bond strength belonged to the control group (14.4760 MPa) and the lowest belonged to the TAP group (11.5808 MPa). The mean bond strength in CH group was less than that of the control and higher than that of the TAP group (11.7834 MPa). However, the difference among the three groups was not statistically significant (p=0.327). Conclusion: Use of medicaments such as CH and TAP has no effect on bond strength of composite to dentin.